2019
DOI: 10.1186/s40659-019-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

De novo in vitro shoot morphogenesis from shoot tip-induced callus cultures of Gymnema sylvestre (Retz.) R.Br. ex Sm

Abstract: BackgroundGymnema sylvestre is a medicinal woody perennial vine known for its sweetening properties and anti-diabetic therapeutic uses in the modern and traditional medicines. Its over-exploitation for the therapeutic uses and to meet the demand of pharmaceutical industry in raw materials supply for the production of anti-diabetic drugs has led to considerable decline in its natural population.ResultsAn efficient system of shoot bud sprouting from nodal segment explants and indirect plant regeneration from api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…(Balachandran et al, 1990). The synergistic effect of higher (Isah, 2019). The effect of 1.0 mgl -1 BAP with 0.25 mgl -1 2, 4-D on adventitious shoot proliferation was observed in C. caesia (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…(Balachandran et al, 1990). The synergistic effect of higher (Isah, 2019). The effect of 1.0 mgl -1 BAP with 0.25 mgl -1 2, 4-D on adventitious shoot proliferation was observed in C. caesia (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…The growth of plants in vitro is influenced by factors such as physiological state of the explant, the genotype, the health status of the plant and the culture media. The health status is a very crucial indicator as to how the plant responds in vitro (Isah, 2015(Isah, , 2019. The results indicate that all the genotypes tested for the presence and absence of the cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) were negative indicating that the pre-basic planting materials were free from viruses, therefore certified as healthy.…”
Section: Discussionmentioning
confidence: 99%
“…The response of the explant used in vitro is dependent on its physiological state, the genotype, the culture media and the health status of the explant (Isah, 2019). The medium is critical because it provides the appropriate nutrients that facilitate growth of the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the initial development, the white callus then turned yellowish and at the end of the observation, the green color appeared in certain parts. According to Isah (2019), the formation of green parts in the callus is the beginning of morphogenesis, this is in line with the formation of shoots. Nurchayati et al (2018) previously reported that the combination of BAP 6x10 -6 M with NAA 10 -5 M produces compact green Datura metel L. callus with meristemoid tissue on part of the surface.…”
Section: Callus Colormentioning
confidence: 96%